On the peptide binding affinity changes in population-specific HLA repertoires to the SARS-CoV-2 variants Delta and Omicron. Issue 133 (December 2022) - Chen, Lu-Chun; Nersisyan, Stepan; Wu, Chang-Jiun; Chang, Che-Mai; Tonevitsky, Alexander; Guo, Chin-Lin; Chang, Wei-Chiao
Abstract: Objective: To investigate the changes of Spike protein-HLA binding affinity profiles between the Wuhan strain and two dominant variants, the Delta and the Omicron strains, among the Taiwanese, the British and the Russian populations. Methods: The HLA frequencies and the HLA-peptide binding affinity profiles in the T-CoV database were combined to conduct the study. We focused on the public alleles in the three populations (HLA-A, HLA-B, HLA-C, HLA-DRB1, and/or HLA-DPA1/DPB1 alleles) and the altered peptides of the spike protein (compared to the Wuhan strain) in the Delta G/478K·V1 (B.1.617.2 + AY.1 + AY.2) and the Omicron (BA.1) strains. Results: For the Delta strain, tight bindings of the altered peptides to the HLA alleles decrease in all three populations and almost vanish in the Taiwanese population. For the Omicron strain, tight bindings are mostly preserved for both HLA classes and in the Taiwanese and the British populations, with a slight reduction in HLA class II in the Taiwanese (1.4%), while the Russian population preserves a relatively high fraction of tight bindings for both HLA classes. Conclusion: We comprehensively reported the changes in the HLA-associated SARS-CoV-2 Spike protein peptide binding profiles among the Taiwanese, the British, and the Russian populations. Further studies are needed to understand the immunological mechanisms and the clinical value of our findings. Highlights: Analyzed the changes in SARS-Co-2 Spike protein peptide-HLA binding profiles for the Delta and the Omicron strains as compared to the Wuhan strain Compared the changes among the Taiwanese, the British, and the Russian populations In all three populations, tight bindings to the mutated peptides are reduced for the Delta strain but mostly preserved for the Omicron strain